Methodological innovation for the teaching of TIC in Higher Education - Morales-Urrutia E.K.; Ocaña J.M.; Yánez Rueda, Hugo; Naranjo A.F.N. (My University, 2021)
The inclusion of technology in the different academic spaces of higher education education has allowed the educational process to take another course and for both teachers and students to adapt to these changes and even more so to those that have been experienced around the pandemic of COVID-19. This study shows the methodological approach for the micro-curricular organization of the Information and Communication Technologies subject, based on didactic methodological strategies that seek to achieve learning achievements based on digital tools according to Bloom’s taxonomy. This research has been carried out in a public university in Ecuador with 207 first-semester students divided into 6 groups. Through the methodological application of its four phases: analysis, planning, design and implementation, and evaluation; favorable results have been obtained in meaningful learning achieved with students. As future work it is intended to apply this methodological approach in related subjects in higher education, thus exposing this approach to a process of continuous improvement. © 2021, Associacao Iberica de Sistemas e Tecnologias de Informacao. All rights reserved.
Innovación metodológica para la enseñanza de TIC en educación superior
Keywords: Couple relationship; Forgiveness; Positive affect; Positive cognition; Resilience